Efektivitas Lama dan Metode Blansir terhadap Kadar Antosianin dan Aktivitas Antioksidan Ubi Jalar Ungu (Ipomoea batatas l.) - Laras Budyghifari; Amran Laga; Nandi K. Sukendar; Muhpidah (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2022)
Purple sweet potato, as one of the tubers with a large area of production and utilization in Indonesia, contains bioactive compounds (including anthocyanin) that are beneficial to health. Anthocyanins give purple pigment, which accumulates with other compounds having antioxidant activity. Heat treatment in purple sweet potato processing at certain times and methods resulted in the degradation of different bioactive compounds. Steamed and boiled blanching methods are common t o prevent this damage. Research on the effect of blanching and drying methods on the content of bioactive compounds of purple sweet potato (Ipomoea batatas l.) was carried out through several stages1) the preparation of purple sweet potato slices using a slicer and 2) directly placing it in a container filled with water to avoid oxidation. Inactivation of the browning-causing polyphenol oxidase enzyme was carried out by steaming and boiling at a boiling temperature (above 100°C) with sampling every 5 minutes for 15 minutes. The best treatment was steamed blanching for 5 minutes with anthocyanin levels of 77.64 mg/kg and antioxidants of 134.54 ppm, categorized as weak activity.